2020
DOI: 10.1007/978-981-15-1588-0_11
|View full text |Cite
|
Sign up to set email alerts
|

On Quasi-Categories of Comodules and Landweber Exactness

Abstract: In this paper we study quasi-categories of comodules over coalgebras in a stable homotopy theory. We show that the quasi-category of comodules over the coalgebra associated to a Landweber exact S-algebra depends only on the height of the associated formal group. We also show that the quasi-category of E(n)-local spectra is equivalent to the quasi-category of comodules over the coalgebra A ⊗ A for any Landweber exact S (p) -algebra of height n at a prime p. Furthermore, we show that the category of module objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In particular, he has proved that the right adjoint of a strong monoidal functor is lax monoidal between monoidal ∞-categories in [5]. In [6] we showed that the right adjoint of an oplax monoidal functor is lax monoidal. Haugseng [2] and Hebestreit-Linskens-Nuiten [3] independently proved that the ∞-category Mon…”
Section: Introductionmentioning
confidence: 88%
“…In particular, he has proved that the right adjoint of a strong monoidal functor is lax monoidal between monoidal ∞-categories in [5]. In [6] we showed that the right adjoint of an oplax monoidal functor is lax monoidal. Haugseng [2] and Hebestreit-Linskens-Nuiten [3] independently proved that the ∞-category Mon…”
Section: Introductionmentioning
confidence: 88%
“…Let us also say immediately that in [23] Lurie already proved that the right adjoint of a strong monoidal functor admits a lax monoidal structure, which suffices for a great many applications. Moreover, Torii has more generally produced a lax monoidal structure (but none of the accompanying coherences) on the right adjoint of an oplax monoidal functor in [29], by means of a span category construction. (We compare his construction to ours in [14].…”
Section: Lax Monoidal Adjunctionsmentioning
confidence: 99%
“…In particular, we will extend the explicit description of dual (co)cartesian fibrations to the situation of curved ortho- and Gray fibrations. As an application, we give an explicit description of parametrised adjoints from [HHLN23], extending previous work of Torii [To20].…”
Section: Dualisation and Straightening Of Two-variable Fibrationsmentioning
confidence: 99%